Deciphering the role of temperature in Li+ co-dopant occupancy in BaYF5:Yb3+,Er3+ up-converting nanocrystals and its structure-property relationship - Devi, Suman; Luwang, Meitram Niraj (Journal of Chemical Physics, 2021)
Precision engineering of defects in luminescent nanoscale crystalline materials with lesser controls to design is an area of interest in engineering materials with desired properties. Li+ co-doped BaYF5 nanocrystals were engineered, and temperature as controls for determining the co-dopant occupancies in the host lattice is studied. An observed enhancement in the up-conversion photoluminescence results from the co-dopant occupancy at Ba2+ sites via substitution through the hot injection method, whereas for samples prepared using co-precipitation, photoluminescence quenching was observed, which can be correlated with the Li+ occupancy at the interstitial site near Er3+ and also due to the incorporation of OH-. The crystal lattice deformation as a result of doping and the mechanism for the observed enhancement/quenching of luminescence are studied using x-ray diffraction, x-ray photoelectron spectroscopy, and energy transfer mechanism. Cytotoxicity assay and photoluminescence studies of the synthesized nanocrystals confirm that the material is biocompatible.